PRETREATMENT EFFECT OF BLACK PEPPER SEEDLINGS WITH Pseudomonas, Trichoderma AND MYCORRHIZA ON FOOT ROT DISEASE INCIDENCE - Dono Wahyuno; Dyah Manohara; Octivia Octivia Trisilawati (Buletin Penelitian Tanaman Rempah dan Obat, 2016)
Foot rot disease caused by a Phytophthora capsici is a main constraint of black pepper cultivation in Indonesia. Improving soil microbial community populations are an alternative approach to suppress the disease incidence. The objective of the present study was assessing the soil microbe application on disease incidence. The research was conducted at greenhouse and field site in Bogor and Sukamulya Research Station, Sukabumi, West Java, Indonesia. At the greenhouse: Seedlings of Natar 1 variety derived from a single node cutting were inoculated with:                                       (1) P. fluorescens (Pf); (2) Trichoderma (Tr); (3) P. fluorescens + Trichoderma (Pf+Tr); (4) P. fluorescens + Trichoderma + AM fungus (Pf+Tr+AM); that artificially inoculated with Phytophthora; (5) The untreated treatment (0) and (6) the               P. capsici inoculated (Phy) were used as control. The experiment was arranged in Complete Random Design, repeated three times, with 30 seedlings each. The field trial was performed at foot rot disease endemic site. The seven nodes pepper seedlings that previously inoculated with (1) P. fluorescens (Pf), (2) Trichoderma (Tr), (3) P. fluorescens and Trichoderma (Pf+Tr), (4) P. fluorescens, Trichoderma, and AM fungi (Pf+Tr+AM), and the uninoculated (0) were used as materials. The treatments were arranged in Complete Random Block Design with five plots each, which consist of              16 pepper vines each. Observations were carried out for disease incidence, soil microbes population and plant vegetative growth parameters. The results showed, all tested beneficial soil microbes reduced disease incidence occurrence for greenhouse, however only Trichoderma individual treatment reduced disease incidence lower than the control in the field test.